Designing All‐Inorganic EuO‐Sensitized TiO2 Solar Cell from 4f‐3d Composite Bandgap Structure. Issue 9 (11th August 2021) - Wang, Qian; Zhu, Wenxuan; Pan, Feng; Song, Cheng
Abstract: TiO2 dye‐sensitized solar cells (DSSCs) have blazed a new trail out of traditional silicon‐based photovoltaics. However, extensive applications of DSSCs are limited by the use of organic photosensitizers and liquid electrolytes, which raises strict requirements on dye synthesis and cell encapsulation. Considering the electron‐donating tendency and optical activity of Eu 2+, EuO semiconductor is chosen as inorganic substitution of organic dyes based on Eu 2+ ↔Eu 3+ redox transition. Through first‐principle calculations, 4f‐3d composite bandgap is found in TiO2 /EuO heterostructure, reducing the bandgap of pure TiO2 from 3.2 to 0.99 eV. This energy corresponds to near‐infrared photon and thus covers the whole range of visible light, which will significantly enhance the light‐absorption efficiency of TiO2 . Similar electronic feature also appears in A TiO3 ( A = Sr, Ba)/EuO interfaces. The bandgap value is critically dependent on bonding type and geometry structure of TiO6 octahedra at the interface. On this basis, all‐inorganic EuO‐sensitized TiO2 solar cell is theoretically designed, where EuO serves as photosensitizer to replace dye molecules and inject electrons into TiO2 anode under light excitation. This finding not only provides prospect for all‐inorganic DSSCs, but also sheds light on high‐efficiency TiO2 ‐based photocatalysis and EuO‐relevant spintronics with rich interfacial physics. Abstract : Traditional TiO2 dye‐sensitized solar cells (DSSCs) usually rely on organic photosensitizers and liquid electrolytes, raising strict requirements on dye synthesis and cell encapsulation. Harnessing 4f‐3d composite bandgap feature ( E g ≈ 1 eV) of TiO2 /EuO heterostructure, the all‐inorganic DSSC is designed based on interfacial charge excitation and redox mechanism, in which EuO photosensitizer replaces organic dyes.